2021
DOI: 10.1021/acs.energyfuels.1c01517
|View full text |Cite
|
Sign up to set email alerts
|

Porous NiCo2O4–FeCo2O4 Nanowire Arrays as Advanced Electrodes for High-Performance Flexible Asymmetric Supercapacitors

Abstract: Efficient supercapacitors have attracted wide attention by the exploration of hybrid materials integrating the merits of individual components as promising electrode materials. However, the construction of advanced hybrid structures for highly enhanced electrochemical energy storage is still challenging. Herein, integration of a strong compositional synergy between various bimetallic oxides, MCo2O4 (M = Ni, Fe, and so on), and inducing rich defects for more redox sites are proposed. A novel NiCo2O4–FeCo2O4 hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Asymmetric stretching of the P–O–P bonds is detected at 905 cm –1 . M–OH absorbs in the regime 700–500 cm –1 , and the peak at 573 cm –1 can be correlated to the bending of Ni–O–H and due to the asymmetric bending vibration of PO 4 . …”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Asymmetric stretching of the P–O–P bonds is detected at 905 cm –1 . M–OH absorbs in the regime 700–500 cm –1 , and the peak at 573 cm –1 can be correlated to the bending of Ni–O–H and due to the asymmetric bending vibration of PO 4 . …”
Section: Resultsmentioning
confidence: 91%
“…The peak at 1116 cm –1 is owing to the asymmetric stretching of PO 4. Vibrational bands of PO 4 3– are observed around 1093, 1026, and 994 cm –1 , corresponding to tetrahedral stretching vibrations. Asymmetric stretching of the P–O–P bonds is detected at 905 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Tong et al constructed a hierarchically constructed anode where a Fe 2 O 3 shell anchored on a CuO core has been deposited onto a carbon cloth current collector. Here the carbon cloth was chosen as a current collector, due to its efficient conductive pathways for electronic conduction (T. Wu, Zhou, et al, 2021). Xinyi et al reported an asymmetric supercapacitor by employing an anode of FeCo 2 O 4 @Ppy (polypyrrole) core/shell nanowires grown onto carbon cloth in a flexible supercapacitor.…”
Section: Carbon Clothmentioning
confidence: 99%